Assessing competence in medicine and other health professions - Violato, Claudio (Boca Raton, Florida CRC Press, 2019)
"This comprehensive, yet accessible, text demystifies the challenging area of competence assessement in medicine and the health sciences, providing a clear framework and the tools for anyone working or studying in this area. Written by a single, highly experienced, author, the content benefits from uniformity of style and is supported and enhanced by a range of pedagogic features including cases, questions and summaries. Essential reading for all students and practitioners of medical education, it will also be an invaluable guide for allied health professionals and psychologists with a general interest in assessment, evaluation and measurement and a useful library reference."
Section I Foundations -- Chapter 1 Introduction -- Chapter 2 Competence and professionalism in medicine and the health professions -- Chapter 3 Statistics and test score interpretation -- Chapter 4 Correlational-based methods -- Section II Validity and Reliability -- Chapter 5 Validity I: Logical/Face and content -- Chapter 6 Validity II: Correlational-based -- Chapter 7 Validity III: Advanced methods for validity -- Chapter 8 Reliability I: Classical methods -- Chapter 9 Reliability II: Advanced methods -- Section III Test Construction and Evaluation -- Chapter 10 Formats of testing for cognition, affect, and psychomotor skills -- Chapter 11 Constructing multiple-choice items -- Chapter 13 Objective structured clinical exams -- Chapter 14 Checklists, rating scales, rubrics, and questionnaires -- Chapter 15 Evaluating tests and assessments: Item analyses -- Chapter 16 Grading, reporting, and standard testing.
Includes bibliographical references and index.
Keywords: Test construction; Educational measurement; Formative feedback; Professional competence; Clinical competence; Assessment